Upaya Guru dalam Bimbingan Belajar Baca Tulis Al-Qur’an Kelas VII Pada Mata Pelajaran Al-Qur’an Hadits di MTSN 01 Solok - Azanni Siska; Muhiddinur Kamal; Darul Ilmi; Nurhasnah Nurhasnah (Pusat Riset dan Inovasi Nasional, 2023)
Researchers conducted research at MTsN 01 Solok against the background of the current many complaints from educators regarding the teaching of Al-Qur'an Hadith material, especially in terms of reading the Al-Qur'an. This research aims to find out how many students still do not read the Al-Qur'an fluently and the efforts made by teachers to overcome this problem at MTsN 01 Solok. These problems are researched using descriptive qualitative research methods which are aimed at describing and analyzing phenomena and events, social activities, attitudes, beliefs, thoughts of people individually and in groups using field research. To analyze the data, researchers grouped it based on existing problems. Based on the findings of research conducted by researchers, it shows that several obstacles faced by students at MTsN 01 Solok regarding Tutoring for Learning to Read and Write Al-Qur'an, one of which is that many of the students are not correct in pronouncing Makhorijul letters, fluency in reading Al-Qur'an. -Qur'an, provisions on recitation and methods in writing the Koran. The efforts made by the teacher in tutoring to read and write the Al-Qur'an before starting learning are that the teacher applies before starting the first 10 minutes of learning, students are asked to read the Al-Qur'an in turns and other students listen before learning begins.